2009
DOI: 10.1590/s0037-86822009000500017
|View full text |Cite
|
Sign up to set email alerts
|

Visceral leishmaniasis in Rio de Janeiro, Brazil: eco-epidemiological aspects and control

Abstract: From 1977 (index case) to 2006, 87 cases of visceral leishmaniasis were confirmed in the municipality of Rio de Janeiro, Brazil, in periurban areas on the continental and coastal slopes of the Pedra Branca massif and the continental slopes of the Gericinó massif. The majority (65.5%) of the patients were more than five years old, predominantly males (61.5%), but without any difference between the sexes below the age of 14 years. The overall fatality rate was 10.4%. Two cases of visceral leishmaniasis/human imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0
29

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(85 citation statements)
references
References 31 publications
1
55
0
29
Order By: Relevance
“…This rate of prevalence was higher than data reported in other studies accomplished in the same municipality FONTES, 2007;ALMEIDA et al, 2009), and the reason may be that there were human cases of the disease reported in the same neighborhood. According to Marzochi et al (2009) the canine disease tends to precede human cases, which are kept high in endemic areas. The presence of about 22% of leishmaniasis seropositive dogs is an important datum for the epidemiological surveillance of Cuiabá.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This rate of prevalence was higher than data reported in other studies accomplished in the same municipality FONTES, 2007;ALMEIDA et al, 2009), and the reason may be that there were human cases of the disease reported in the same neighborhood. According to Marzochi et al (2009) the canine disease tends to precede human cases, which are kept high in endemic areas. The presence of about 22% of leishmaniasis seropositive dogs is an important datum for the epidemiological surveillance of Cuiabá.…”
Section: Discussionmentioning
confidence: 99%
“…Environments degraded by disordered occupation have been described as another risk factor that facilitates the occurrence of CVL (MISSAWA;BORBA, 2009;MARZOCHI et al, 2009). The highest indexes of IFAT seropositive animals were observed in the neighborhoods located in rural environments and in the Jardim União neighborhood, which presented severe natural ecotope changes and where human cases of the disease were reported (personal communication).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite the continuity of the program, but with the help of pyrethroids instead of DDT, infection among dogs is reemerging 44 . Another successful experience in Brazil occurred in a small outbreak in Rio de Janeiro, between 1979 and 1985 45 , where they used organochlorines, followed by pyrethroids. However, there was no interruption of the transmission.…”
Section: New Worldmentioning
confidence: 99%
“…In 2011, another CVL case was described in Cachoeiras de Macacu, Rio de Janeiro (SILVA et al, 2011). Although the case was not autochthonous, it may have contributed to maintain the cycle in the region, since the presence of susceptible sand flies associated with human and canine migration, disorganized land occupation leading to the environmental degradation of protected areas, and low socioeconomic conditions may cause an epidemic (MARZOCHI et al, 2009). …”
Section: Introductionmentioning
confidence: 98%